Effectiveness of melatonin treatment for sleep disturbance in orthopaedic trauma patients: A prospective, randomized control trial. Issue 12 (December 2022) - Tanner, Natalie; Schultz, Blake; Calderon, Christian; Fithian, Andrew; Segovia, Nicole; Bishop, Julius; Gardner, Michael
Abstract: Objectives: Explore sleep disturbance in postoperative orthopedic trauma patients and determine the impact of melatonin supplementation on postoperative sleep, pain, and quality of life. Materials and Methods: In this prospective, randomized controlled trial at a Level I trauma center, 84 adult orthopedic trauma patients with operative fracture management were randomized 2-weeks postoperatively to either the melatonin or placebo group. Patients randomized to the melatonin group (42 subjects, mean age 41.8 ± 15.5 years) received 5 mg melatonin supplements. Patients in the placebo group (42 subjects, mean age 41.3 ± 14.0 years) received identical glucose tablets. Both groups were instructed to take the tablets 30 minutes before bed for 4 weeks and received sleep hygiene education and access to the Cognitive Behavioral Therapy for Insomnia (CBT-I) Coach app. Main Outcome Measures: Our primary outcome was sleep quality as measured by the Pittsburgh Sleep Quality Index (PSQI). Secondary outcomes were pain measured by the Visual Analog Scale (VAS), quality of life measured by the 36-Item Short Form Survey (SF-36), and opioid use. Results: Patients in both groups had significant sleep disturbance (PSQI ≥ 5) at 2-weeks (83%) and 6-weeks (67%) postoperatively. PSQI improved by 3.3 points (p<0.001) at follow-up, but there was no significant difference between groups (melatonin PSQI = 5.6, placebo PSQI = 6.1, P = 0.615). Compared to placebo, melatonin did not affect VAS, SF-36, or opioid use significantly. Conclusion: Sleep disturbance is prevalent in orthopedic trauma patients. Melatonin treatment did not significantly improve subjective sleep quality, pain, quality of life or opioid use. Level of evidence: Therapeutic Level I.